Guardians of consent: enhancing rape prevention through social control mechanisms - Bhattacharya, Sudip; Singh, Amarjeet (Frontiers in Sociology, 2024)
IntroductionRape is a severe violation involving non-consensual sexual acts, often accompanied by force, threats, or coercion, leading to profound physical, emotional, and social consequences for survivors.AimThis review aims to examine and synthesize research on effective strategies for rape prevention and intervention, with a particular focus on social control mechanisms, legal frameworks, cultural change, educational programs, public awareness campaigns, community vigilance, victim support services, and the influence of digital media.MethodologyA comprehensive review was conducted by searching PubMed, Scopus, PsycINFO, and Google Scholar for peer-reviewed articles, policy papers, and reports from the past 20 years. Keywords like “rape prevention,” “legal frameworks,” and “consent education” were used with Boolean operators to refine the focus. Articles addressing prevention strategies, social control, legal reforms, or public awareness with empirical findings or theoretical insights were included, while unrelated studies were excluded. From 6500 records, 39 studies were ultimately included after screening and eligibility assessments.ResultsThe global and national burden of rape is substantial, with significant prevalence differences influenced by cultural, socio-economic, and legal factors. Effective prevention of rape necessitates a multifaceted approach that includes stringent legal frameworks, comprehensive education on consent, public awareness campaigns, social control, and community vigilance.DiscussionSocial control plays a critical role in these prevention strategies, encompassing both formal mechanisms like legal sanctions and informal controls such as societal norms and cultural attitudes. Challenges to these efforts include persistent rape myths, victim-blaming, inconsistent legal definitions of consent, and the evolving complexities of digital media. However, global examples such as Sweden’s consent-based legal reforms and the UK’s cultural shift through public campaigns demonstrate that these challenges can be addressed effectively. National efforts, including the “It’s On Us” campaign in the United States and legal reforms in India, further highlight the importance of tailored interventions to address specific contextual challenges.ConclusionUltimately, overcoming these challenges requires an integrated strategy that combines legal reforms, educational initiatives, cultural change, and robust support systems for survivors. By learning from successful global and national models, societies can build more effective frameworks for preventing rape and ensuring justice for those affected.